DIGITAL TRANSFORMATION AS AN APPROACH TO ENHANCING SUSTAINABLE COMPETITIVE ADVANTAGE IN THE PERFORMANCE OF EDUCATIONAL INSTITUTIONS: AN ANALYTICAL STUDY IN SOME COLLEGES OF THE HOLY UNIVERSITY IN KARBALA: TRANSFORMASI DIGITAL SEBAGAI PENDEKATAN UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF BERKELANJUTAN DALAM KINERJA LEMBAGA PENDIDIKAN: STUDI ANALITIS DI BEBERAPA PERGURUAN TINGGI DI UNIVERSITAS SUCI DI KARBALA - Abbas Jasim Mohammad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital transformation has become a strategic approach for organizations seeking improved operational systems and competitive positioning through the integration of advanced technologies, digital strategies, and data-driven management. Specific Background: In higher education institutions, digital transformation involves technological infrastructure, data and analytics, digital strategy, security, and organizational culture to support institutional performance and competitive advantage dimensions such as quality, service excellence, and customer responsiveness. Knowledge Gap: Despite increasing global attention to digital transformation in universities, empirical studies examining its relationship with sustainable competitive advantage in educational institutions remain limited, particularly within the context of Iraqi higher education. Aims: This study aims to analyze the relationship between digital transformation dimensions and competitive advantage in the performance of educational institutions through a field study conducted in several colleges of the Holy University of Karbala. Results: The findings indicate a statistically significant relationship between digital transformation and competitive advantage dimensions. Digital strategy and data analytics show significant relationships with quality and service excellence, while data and analytics demonstrate a significant relationship with customer responsiveness. Overall results show high levels of digital transformation (mean = 4.00) and competitive advantage (mean = 4.17), with an overall mean of 4.09 indicating strong consensus regarding the role of digital technologies in institutional performance. Novelty: This study provides empirical evidence linking multiple digital transformation dimensions with competitive advantage indicators within university environments. Implications: The results highlight the importance of investing in digital infrastructure, adopting comprehensive digital strategies, and strengthening data-driven decision-making to support institutional performance and long-term competitiveness in higher education. Highlights: Strong institutional agreement regarding digital technology adoption in university operations Data analytics shows a significant relationship with responsiveness to user needs Strategic digital planning demonstrates statistical association with academic service quality Keywords: Digital Transformation; Competitive Advantage; Educational Institution Performance; Data And Analytics; Digital Strategy